THE IGF-1 LEVEL OF ESRD PATIENTS AND ITS RISK FACTORS - Hidayati, Titiek; Yuningtyaswari, Yuningtyaswari; Sadewa, Ahmad Hamim; Soesatyo, Marsetyawan HNE (Indonesian Journal of Urology, 2014)
Objective: To identify the Insulin-like Growth Factor–1 (IGF-1) level of End Stage Renal Disease (ESRD) and non ESRD populations, and correlation between IGF-1level and ESRD incidences. Material & Method: This case study was carried out in Yogyakarta with 72 volunteers. The cases involved Chronic Kidney Disease (CKD) patients. The controls were non-CKD patients. CKD parameters were established with PERNEFRI diagnostic criteria. Comparison of IGF-1 levels between case and control groups was performed through ANOVA, with confidence level of 95%. Bivariate analysis to identify the correlation between IGF-1 plasma level, smoking status, illness history and body mass index (BMI) by determining odds ratio (OR) of individual risk factor of p < 0.05. Results: We enrolled 72 volunteers, 45 male and 27 female subjects. Of the 45 male patients, 15 CKD and 30 non CKD patients served as cases and controls, respectively. The difference in plasma IGF-1 level was detected in the case and control groups (42.01 ± 10.66 vs. 56.05 ± 24.91) (p < 0.05). The result of bivariate analysis showed passive smoking status, IGF-1 plasma level, DM history and hypertensive illness history had correlation with ESRD incidence with odds ratios of 7.88 (p < 0.005; CI: 1.6-37.5) for passive smokers, 4.3 (p < 0.05, CI: 1.36 to 13.33) for IGF-1 level, 21.5 (p < 0.05; CI) for DM history and 12.4 (p < 0.05; CI: 3.7 to 41) for hypertensive history. Conclusion: There was difference in IGF-1 plasma level between ESRD and non-ESRD patients. The IGF-1 plasma level, passive smoking status, diabetes history, and hypertensive history have correlation with ESRD incidence.Keywords: Insulin-like Growth Factor–1 level, End Stage Renal Disease, case control, odds ratio.